Planning Support Systems Best Practice and New Methods
XXII, 490 p.
Keywords: This book is about a particular set of geo-information technologies known as Planning Support Systems (PSS). It focuses on the adoption and application of PSS in practice. It aims to illustrate best practice and to demonstrate new methods that are being developed for creating the next generation of PSS for use in various public or private sector planning contexts. The book serves as a medium for the exchange of knowledge, insights and experiences, thereby preventing those working in this field from having to ‘reinvent the wheel’. It also serves to communicate details about PSS methodology and management to those less informed about contemporary developments. The book stimulates new and exciting applications of PSS in diverse planning situations. It provides planning practitioners, system developers and researchers with helpful insights into what planning support systems are, how they can be constructed and implemented, and in which situations they can provide valuable support for decision making.